Attitudes and Practices of Immune Checkpoint Inhibitors in Chinese Patients With Cancer: A National Cross-Sectional Survey - Zhang, Luping; Wang, Jun; Zhang, Bicheng; Chu, Qian; Su, Chunxia; Wu, Hao; Chen, Xiaobing; Wang, Baocheng; Yin, Yongmei; Zhu, Bo; Sun, Jianguo (Frontiers in Pharmacology, 2021)
Immune-checkpoint inhibitors (ICIs) are revolutionizing the field of immuno-oncology. Side effects and tumor microenvironment currently represent the most significant obstacles to using ICIs. In this study, we conducted an extensive cross-sectional survey to investigate the concept and practices regarding the use of ICIs in cancer patients in China. The results provide real-world data on the adverse events (AEs) of ICIs and the factors influencing the use of ICIs. This survey was developed by the Expert Committee on Immuno-Oncology of the Chinese Society of Clinical Oncology (CSCO-IO) and the Expert Committee on Patient Education of the Chinese Society of Clinical Oncology (CSCO-PE). The surveys were distributed using a web-based platform between 11-29-2019 and 12-21-2019. A total of 1575 patients were included. High costs (43.9%), uncertainty about drug efficacy (41.2%), and no reimbursement from medical insurance (32.4%) were the factors that prevented the patients from using ICIs. The patients were most concerned about the onset time or effective duration of ICIs (40.3%), followed by the indications of ICIs and pre-use evaluation (33.4%). Moreover, 9.0%, 57.1%, 21.0%, and 12.9% of the patients reported tumor disappearance, tumor volume reduction, no change in tumor volume, and increased tumor volume. Among the patients who received ICIs, 65.7% reported immune-related AEs (irAEs); 96.1% reported mild-to-moderate irAEs. Cancer patients in China had a preliminary understanding of ICIs. Yet, the number of patients treated with ICIs was small.